TENDENCY TO ADOPT BLOCKCHAIN TECHNOLOGY IN PORTUGUESE SUPPLY CHAINS - Paulo A. Pereira; Martins, A.; Ferreira, J. (The 25th International Symposium on Logistics (ISL 2021), 2021)
This paper aims to investigate the implementation potential of Blockchain Technology (BCT) for Supply Chain Management (SCM) in Portuguese organizations with the systematization of advantages, disadvantages, and barriers. The research aims at exploring how barriers and the familiarity with BCT are related with advantages, disadvantages and barriers of adopting BCT for SCM and ultimately with the adoption scenario. A systematic literature review (SLR) approach allowed identifying items to build a structured questionnaire to be applied to managers from the food, transportation, and pharmaceutical sectors. Data gathered from 48 companies, analysed through SPSS version 27.0 revealed that the links between the variables are very weak mostly because there is a misunderstanding about BCT.